Frailty Index–CGA and mortality at a 12-month follow-up at Hospital Central de la Fuerza Aérea del Perú - Peralta Vargas, Carmen Eliana (2023)
Objective: To determine the relationship between mortality and level of frailty using the Frailty Index–Comprehensive Geriatric Assessment (FI–CGA) among older adults at a 12-month follow-up. Materials and methods: A descriptive, observational and prospective study with non-probabilistic sampling conducted with patients over 60 years of age from the Geriatrics Service. Using the FI–CGA, frailty was diagnosed if the score was greater than or equal to 0.2 at the different levels of care: acute care unit, day hospital, outpatient clinic and house call. Moreover, a follow-up was conducted 12 months following their telephone consultation. In case of death, the event and cause were confirmed in the Sistema Informático Nacional de Defunciones (SINADEF, National Death Computer System) of the Ministry of Health of Peru. Patients who died from coronavirus complications were excluded. To determine the association between FI–CGA and mortality, chi-square and Student’s t tests were used for the qualitative and quantitative variables, respectively. Results: A total of 241 subjects with an average age of 85.08 years were included in the research. Out of this population, 222 (92.12 %) were classed as frail (FI–CGA score ≥ 0.2), among which 82 were considered mildly frail (0.2–0.36), 59 moderately frail (0.4–0.52) and 54 severely frail (> 0.56). At the 12-month follow-up, 28 (11.61 %) older adults had died during that period. Out of the deceased, 23 (82.14 %) had a FI–CGA score greater than or equal to 0.56. When analyzing the association between mortality and the FI–CGA, it was found that the higher the FI, the higher the mortality, with very significant differences (p = 0.001). There was no association between age and mortality (p = 0.95). Conclusions: The FI–CGA is a useful tool to predict mortality in frail patients, according to their severity, at a 12-month follow-up.